2000
DOI: 10.1038/sj.ejcn.1601033
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in the elderly

Abstract: Adiposity increases with age. The size of the adipose tissue mass is determined by the balance between the recruitment of lipid substrates (ie free fatty acids) from adipose tissue and their subsequent oxidation by respiring tissues. Thus, change in the liberation of free fatty acids from adipocytes, the capacity of respiring tissue to oxidize free fatty acids or a combination of both may contribute to the age-related increase in body fat. This review focuses on studies that have examined the effect of age on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(104 citation statements)
references
References 39 publications
(55 reference statements)
8
92
1
3
Order By: Relevance
“…Of course, this does not exclude the possibility that insulin or leptin have different effects on energy intake according to age. It has been reported that, in normal body weight subjects, aging is associated with a lower lipolytic capacity (Toth & Tcherof, 2000), in particular after sympathetic stimulation (Blaak, 2000), and this could explain the increased adipose tissue deposition of older subjects. Furthermore, a blunted lipolytic activity has been described in obese, post-menopausal women submitted to hypocaloric diet (Nickals et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this does not exclude the possibility that insulin or leptin have different effects on energy intake according to age. It has been reported that, in normal body weight subjects, aging is associated with a lower lipolytic capacity (Toth & Tcherof, 2000), in particular after sympathetic stimulation (Blaak, 2000), and this could explain the increased adipose tissue deposition of older subjects. Furthermore, a blunted lipolytic activity has been described in obese, post-menopausal women submitted to hypocaloric diet (Nickals et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the most simplistic way it appears that reproductive function and insulin resistance, both of which are associated with accelerated aging, are also closely related to body fat mass and are both affected by hormones produced by adipocytes (Mora and Pessin, 2002). Moreover, free fatty acids released constantly into the circulation, especially from visceral WAT by its relative high number of β-adrenoceptors, induce insulin resistance when not oxidized immediately as is the case in the elderly (Toth and Tchernof, 2000;Möller and Kaufmann, 2005. Interestingly, human adipocytes show an increased expression of SIRT1 when they are incubated in serum from calorie-restricted rats, whereas both insulin and IGF-1 are to suppress SIRT1 up-regulation when added to the serum .…”
Section: Molecular Links Of Cr and Aging Molecular Links Of Cr And Agmentioning
confidence: 99%
“…Figure 1 shows the age-related changes in free fatty acid metabolism in older humans. Until now, few animal or human studies have shown that ageing affects the stimulation, release and activity of fat metabolism-relevant hormones with a serious negative impact on the rate of lipolysis, as well as whole body composition [38]. One reason for this occurrence might be the age-related reduced insulin release from pancreatic tissue.…”
Section: Fat Metabolismmentioning
confidence: 99%